2005
DOI: 10.1111/j.1468-2982.2005.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan Causes Parallel Decrease in Plasma Calcitonin Gene-Related Peptide (CGRP) Concentration and Migraine Headache During Nitroglycerin Induced Migraine Attack

Abstract: Sumatriptan-induced changes in plasma calcitonin gene-related peptide (CGRP) concentration and headache intensity were investigated in 19 female migraineurs during nitroglycerin-induced migraine attack. Sumatriptan nasal spray was administered 120 min after the onset of the attack. Blood samples were obtained immediately before and 60 min after sumatriptan administration. In those subjects whose migraine attack improved considerably 60 min after the treatment the plasma CGRP concentration decreased significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
147
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 31 publications
6
147
1
3
Order By: Relevance
“…62,63 In addition, nitroglycerine did not elicit cluster headache attacks if the patient was not in a prone status (i.e., a state in which the disease was active and a small stimulation could then elicit the full cluster headache attack). Studies of the perfused middle cerebral artery 4,61,64 showed that CGRP does not readily pass the blood-brain barrier, which agrees well with this supposition; the nerve fibers are situated in the adventitia and act on the receptors located in the smooth muscle cells. Thus, a low degree of perivascular CGRP release likely occurs in mild to mod-erate attacks, but it is necessary to have a large release to measure the peptide in the cranial venous effluent.…”
Section: Neurotransmitter Release In Migrainesupporting
confidence: 72%
See 2 more Smart Citations
“…62,63 In addition, nitroglycerine did not elicit cluster headache attacks if the patient was not in a prone status (i.e., a state in which the disease was active and a small stimulation could then elicit the full cluster headache attack). Studies of the perfused middle cerebral artery 4,61,64 showed that CGRP does not readily pass the blood-brain barrier, which agrees well with this supposition; the nerve fibers are situated in the adventitia and act on the receptors located in the smooth muscle cells. Thus, a low degree of perivascular CGRP release likely occurs in mild to mod-erate attacks, but it is necessary to have a large release to measure the peptide in the cranial venous effluent.…”
Section: Neurotransmitter Release In Migrainesupporting
confidence: 72%
“…66,67 In addition, after sumatriptan or rizatriptan administration, the plasma levels of CGRP returned to control levels, with successful amelioration of the headache. 4,61,64 These results have been confirmed in experimental studies using zolmitriptan, rizatriptan, sumatriptan, and dihydroergotamine. The 5-HT 1B/1D receptors are expressed on human trigeminal ganglion cells and on trigeminal sensory fibers, 68 thus providing sites for presynaptic inhibition of the CGRP release and of contractile 5-HT 1B receptors in intracranial arteries.…”
Section: Neurotransmitter Release In Migrainesupporting
confidence: 69%
See 1 more Smart Citation
“…Most notably, systemic administration of CGRP induces migraine-like symptoms among migraineurs (7), and a CGRP receptor antagonist can attenuate migraine (8). The possibility that CGRP synthesis is elevated during migraine is suggested by elevation of serum CGRP levels during spontaneous migraine (9,10). Given the generally long duration of migraine, it seems reasonable that these elevated CGRP levels might be sustained by increased transcription.…”
mentioning
confidence: 99%
“…A correlation was detected between the CGRP level, the timing of the attack and the severity of the pain. The influence of CGRP in migraine headache is validated by the administration of triptans, which successfully ameliorate the attacks, the level of CGRP returning to the control [19].…”
Section: Transmitters Neuropeptides and Sensitizationmentioning
confidence: 99%